Performance optimisation through EPT-WBC in mobile ad hoc networks. Issue 3 (3rd March 2016) - Agarwal, Ratish; Gupta, Roopam; Motwani, Mahesh
Abstract : Mobile ad hoc networks are self-organised, infrastructure-less networks in which each mobile host works as a router to provide connectivity within the network. Nodes out of reach to each other can communicate with the help of intermediate routers (nodes). Routing protocols are the rules which determine the way in which these routing activities are to be performed. In cluster-based architecture, some selected nodes (clusterheads) are identified to bear the extra burden of network activities like routing. Selection of clusterheads is a critical issue which significantly affects the performance of the network. This paper proposes an enhanced performance and trusted weight-based clustering approach in which a number of performance factors such as trust, load balancing, energy consumption, mobility and battery power are considered for the selection of clusterheads. Moreover, the performance of the proposed scheme is compared with other existing approaches to demonstrate the effectiveness of the work.